Does dispersal influence the strength of intraspecific competition in a stream salamander?. (19th August 2015) - Davenport, J. M.; Lowe, W. H.
Abstract: Metacommunity ecology emphasizes the role of dispersal in linking local processes across space. Competition is one such local process that can be affected by dispersal. Dispersal can influence intraspecific trait variation, thereby affecting the strength of intraspecific competition and, consequently, the relative importance of intra‐ versus interspecific interactions. Prior research has shown that spring salamanders, G yrinophilus porphyriticus, self‐organize within streams by a common trait (body condition) and that dispersal and gene flow along streams vary with slope. Building on this prior work, we tested how dispersal influences the strength of intraspecific competition via one of two spatial mechanisms: (1) spatial sorting of individuals by traits that affect competitive performance or (2) variation in gene flow resulting in evolutionary divergence of traits affecting competitive performance. To test these alternative mechanisms, we conducted a mesocosm experiment with spring salamanders from downstream and upstream sites of streams with low and high rates of dispersal and gene flow. Spatial patterns of intraspecific competitive performance differed significantly in the low‐ and high‐dispersal streams. In the low‐dispersal stream, downstream individuals were better intraspecific competitors than upstream individuals, whereas the opposite was true in the high‐dispersal stream. These differences support the spatial sorting mechanism, reinforcing direct dispersal data showing that high‐performance individuals are more likely to move upstream in the high‐dispersal stream and to remain downstream in the low‐dispersal stream. To our knowledge, this is the first time that spatial sorting has been explicitly identified as contributing to the strength of intraspecific interactions. Our study underscores the importance of integrating natural rates of dispersal into mechanistic experiments to understand spatial variability in the strength of intra‐ and interspecific species interactions.